ULTRASONIC DIAGNOSIS OF CEREBROVASCULAR DISEASE IN THE ASPHYXIA OF NEWBORN - Z. A. Agaeva (Кубанский научный медицинский вестник, 2017)
Aim. To detect the most informative ultrasonic signs of cerebral haemodynamics distress in various degrees of severity asphyxia of newborn for the timely correction of cerebral haemodynamics and normal morphofunctional maturation of brain structures in the early neonatal period and childhood.Materials and methods. 78 newborns were examined, including: 25 newborns who had a satisfactory condition at birth and 53 newborns with a mild, moderate and severe condition at birth due to neonatal asphyxia. Ultrasonic examination of brain and Doppler sonography of cerebral blood flow were carried out for all newborns in the first 7 days of life.Results. Echographic and Doppler sonographic criteria of changes in cerebral haemodynamics of full-term newborn with mild, moderate and severe asphyxia were obtained.Conclusion. Cranial ultrasound demonstrates dopplerographic signs of cerebral hemodynamics formation disorders such as hypoperfusion in neonates who have had chronic intrauterine hypoxia in the early neonatal period, and signs of cerebral hyperperfusion in neonates who suffered from acute asphyxia. In neonates who have suffered from acute asphyxia against a background of chronic intrauterine hypoxia, signs of hypoperfusion persisted for a longer period as compared to neonates with chronic intrauterine hypoxia.